Efeitos da infusão contínua de Cetamina s(+) em equinos anestesiados pelo Halotano - Borges, José Henrique Saraiva [UNESP]; Souza, Adriana Helena de [UNESP]; Dória, Renata Gebara Sampaio [UNESP]; Canola, Júlio Carlos [UNESP]; Santos, Paulo Sergio Patto dos [UNESP]; Valadão, Carlos Augusto Araújo [UNESP] (FapUNIFESP (SciELO), 2010)
The horse’s blood pressure is susceptible to changes induced by volatile anesthetics. Because of that, the use of anesthesic techniques which keep stable the horse´s blood pressure is essencial. Ketamine is an important induction and maintenance anesthetic agent used in the horse anesthesia practice mainly to improve the blood pressure. S(+)-ketamine provides the same effects on the blood pressure, with greater analgesic results and less side effects than the normal ketamine. Although some studies have been conducted with ketamine continuous rate infusion during the halothane anesthetized horses, the S(+)-ketamine has not been evaluated yet. Considering the increased use of ketamine, it is important to evaluate its cardiovascular and respiratory effects in halothane anesthetized horses. To conclude, S(+)-ketamine 0.01mg/kg/min. continuous rate infusion did not induce additive cardiovascular and respiratory depression in halothane anesthetized horses.

A manutenção da pressão arterial, no transanestésico, consiste grande desafio, principalmente quando se trata da espécie equina, suscetível à instabilidade cardiovascular. Por isso, torna-se imperioso utilizar técnica anestésica que mantenham estáveis os parâmetros cardiovasculares. A cetamina tem sido amplamente empregada na indução anestésica para o halotano em equinos, conferindo-lhes estabilidade cardiovascular. A cetamina S(+), recentemente disponibilizada no mercado, induz estimulação cardiovascular e possui maior potência anestésica e analgésica em relação à cetamina. Todavia, os efeitos dessa substância, administrada por infusão contínua durante a manutenção da anestesia pelo halotano em equinos, ainda não foram avaliados. Em face da tendência atual de a infusão continuada da cetamina potencializar os anestésicos inalatórios, considerou-se pertinente avaliar os efeitos cardiovasculares e respiratórios desse isômero de cetamina em equinos anestesiados pelo halotano. Conclui-se que a infusão contínua de 0,01mg/kg/min de cetamina S(+) durante anestesia com 1,5 CAM de halotano em equinos não agravou a depressão cardiorrespiratória promovida por esse anestésico inalatório.
Effects of s(+)-ketamine continuous rate infusion in horses anesthetized by Halothane
Keywords: S(+)-ketamine; Horses; Halothane; Continuous rate infusion; Cetamina S(+); Equinos; Halotano; Infusão contínua